Very long-term survival and late sudden cardiac death in cardiac resynchronization therapy patients. (2nd May 2019) - Barra, Sérgio; Duehmke, Rudolf; Providência, Rui; Narayanan, Kumar; Reitan, Christian; Roubicek, Tomas; Polasek, Rostislav; Chow, Antony; Defaye, Pascal; Fauchier, Laurent; Piot, Olivier; Deharo, Jean-Claude; et al.
Abstract: Aims: The very long-term outcome of patients who survive the first few years after receiving cardiac resynchronization therapy (CRT) has not been well described thus far. We aimed to provide long-term outcomes, especially with regard to the occurrence of sudden cardiac death (SCD), in CRT patients without (CRT-P) and with defibrillator (CRT-D). Methods and results: A total of 1775 patients, with ischaemic or non-ischaemic dilated cardiomyopathy, who were alive 5 years after CRT implantation, were enrolled in this multicentre European observational cohort study. Overall long-term mortality rates and specific causes of death were assessed, with a focus on late SCD. Over a mean follow-up of 30 months (interquartile range 10–42 months) beyond the first 5 years, we observed 473 deaths. The annual age-standardized mortality rates of CRT-D and CRT-P patients were 40.4 [95% confidence interval (CI) 35.3–45.5] and 97.2 (95% CI 85.5–109.9) per 1000 patient-years, respectively. The adjusted hazard ratio (HR) for all-cause mortality was 0.99 (95% CI 0.79–1.22). Twenty-nine patients in total died of late SCD (14 with CRT-P, 15 with CRT-D), corresponding to 6.1% of all causes of death in both device groups. Specific annual SCD rates were 8.5 and 5.8 per 1000 patient-years in CRT-P and CRT-D patients, respectively, with no significant difference between groups (adjusted HR 1.0, 95% CI 0.45–2.44). Death due to progressive heart failure represented the principal cause of death (42.8% in CRT-P patients and 52.6% among CRT-D recipients), whereas approximately one-third of deaths in both device groups were due to non-cardiovascular death. Conclusion: In this first description of very long-term outcomes among CRT recipients, progressive heart failure death still represented the most frequent cause of death in patients surviving the first 5 years after CRT implant. In contrast, SCD represents a very low proportion of late mortality irrespective of the presence of a defibrillator.